How Can Criminology and Victimology Answer the Protection of Victims of Domestic Violence? (Faculty of Law Universitas Negeri Semarang, 2022)
The term violence is used to describe behavior, whether overt, or covert, either offensive or defensive, which is accompanied by the use of force to others. Law No. 23 of 2004, defines domestic violence as any act against a person, especially a woman, which results in physical, sexual, psychological, and/or domestic neglect or suffering including threats to commit acts, coercion, or unlawful deprivation of independence within the scope of the household. This study aims to analyze how criminology and victimology are able to answer victim protection in cases of domestic violence in Indonesia. This study uses normative affirmations using legal studies, criminology, and victimology in cases of domestic violence.